Gambaran pengetahuan dan penerapan personal hygiene siswa dalam upaya mencegah infeksi soil transmitted helminth (STH) - Kusumarini R, Shelly; Sholekhah, Salas Salma; Vandania, Fane; Lazulfa, Zaky Indana (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2021)
Cases of intestinal worms or often referred to as neglected tropical diseases are a global problem that occurs in society. Groups of school-age children are more susceptible to being infected by parasitic worms transmitted through the soil (Soil-Transmitted Helminth). The dangers of STH infection in children are impaired nutrient absorption, malnutrition, weight loss, and cognitive decline. The problem at SDN Karangkembang is that student activities are closely related to the risk factors of STH transmission, namely, playing sand without footwear, not washing hands, hawker vendors around the school who are less hygienic. Also, there are no adequate handwashing facilities in schools. Based on these problems, the Faculty of Veterinary Medicine, UB initiated a community service program namely worm socialization and prevention efforts through the application of personal hygiene. The results obtained during this community service activity are that 83% of students have carried out the practice of cleanliness very well, then 9% of students have carried out well, 4% of students carry out adequately and 4% of students are still lacking. This community service activity can coordinate all students, teachers, and parents to commit to always apply personal hygiene to improve the quality of life both at school and at home.